Expectations of self-efficiency and its relation to life skills at teachers of secondary schools (Journal of the College of Education for Women, 2019)
Research aims1. Measuring expectations of self-efficiency at teachers of secondary schools.2. Measuring biological skills at teachers of secondary schools.3. There is no sole or gathering forecasting of forecasting expectations of self-efficiency , may forecasts about biological skills at teachers of secondary schools.To fulfill aims of the research, the researcher managed measuring of expectations of self-efficiency according to point of view of Bandura for this concept in this research, arranging measure of biological skills according to view of global health, the researcher has made to investigate of truth , constant these two measurements, analyzing statistically their two paragraphs on a sample (460) teachers (males & female) from Karkh 2, Rasafa 2, they were chosen by layer randomly method , with equal method, to analyze results of the research, the researcher uses a group of statistical means as (T-test for two independent sample , coefficient of person linking , Alpha Chronbach equation , analyzing multi-steep )The researcher has concluded the following results: The teachers of secondary schools are interesting with good level of expectations of self-efficiency. The teachers of secondary schools are interesting with good level of biological skills. There is sole or gathering forecasting of forecasting expectations of self-efficiency , may forecasts about biological skills at teachers of secondary schools.